1994
DOI: 10.1099/0022-1317-75-9-2379
|View full text |Cite
|
Sign up to set email alerts
|

Oral-oesophageal inoculation of mice with herpes simplex virus type 1 causes latent infection of the vagal sensory ganglia (nodose ganglia)

Abstract: Herpes simplex virus type 1 (HSV-1) gingivostomatitis during childhood is known to result in a latent infection of the trigeminal ganglion neurons, which innervate the oral mucosa. During latency the viral genome is maintained in a non-infectious state. However, stimuli such as stress, fever or localized trauma can cause HSV-1 to reactivate in neurons and produce recrudescent disease in the peripheral tissues. Recently, HSV-1 proteins and nucleic acids have been detected in biopsies from human duodenal and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Although the trigeminal ganglia represent the primary site where HSV-1 resides in the latent form (33), other locations have been documented, including the nodose ganglion of the vagus nerve (18), the dorsal root ganglia (20), the sympathetic ganglia (51), and the brain (3,47). Thus, the spinal cord and brain could act as reservoirs of latent virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the trigeminal ganglia represent the primary site where HSV-1 resides in the latent form (33), other locations have been documented, including the nodose ganglion of the vagus nerve (18), the dorsal root ganglia (20), the sympathetic ganglia (51), and the brain (3,47). Thus, the spinal cord and brain could act as reservoirs of latent virus.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all adults show evidence of having been infected by HSV-1, its genome residing latently in the trigeminal ganglia and in the CNS of both healthy individuals and those suffering from neurological disease (14). The trigeminal ganglion is the primary site of HSV-1 latency, although other sites including the sensory neurons (33) and other sensory ganglia such as the nodose ganglion of the vagus nerve (18), the dorsal root ganglia (20), the sympathetic ganglia (51), and the brain may be involved (3,47). The persistence of HSV-1 in nonneuronal tissue has also been suggested but remains controversial (33).…”
mentioning
confidence: 99%
“…infected cell proteins, ICP0, ICP4, ICP22, and ICP27) responsible for regulating viral gene expression during subsequent phases of the replication cycle [6]. Gesser et al (1994, 1995, 1996) showed that in mice HSV-1 orally inoculated was able to establish latency in the nodose ganglia of the vagus nerve or spread through the myenteric, submucosal, and periglandular plexuses leading to progressive inflammatory disease and death [7]–[9]. HSV-1 shedding from the oropharyngeal mucosa occurs in chronically infected human subjects thus facilitating virus passage to the gastrointestinal tract mucosa where it infects the nodose and celiac ganglia.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigators agree that the trigeminal ganglion is the primary site of HSV-1 latency (Stevens and Cook, 1971;Bastian et al, 1972;Baringer and Swoveland, 1973;Plummer, 1973;Cook et al, 1974;Walz et al, 1974;Warren et al, 1978;McLennan and Darby, 1980;Kennedy et al, 1983;Price, 1986;Stevens, 1989a). However, additional sites of latency have been reported and include other sensory ganglia such as the nodose ganglion of the vagus nerve (Gesser et al, 1994), dorsal root ganglia (Hill et at., 1975) as well as sympathetic ganglia (Warren et at., 1978), and the brain (Sequiera et at., 1979;Baringer and Pisani, 1994). The persistence of HSV-1 in non-neuronal tissue has support from several studies (Shimeld et al, 1982;Openshaw, 1983;Tullo et al, 1985;Abghari and Stulting, 1988;Sabbaga et al, 1988;Cook et al, 1991;Openshaw et at., 1995) but remains controversial.…”
Section: Hsv-1 Latencymentioning
confidence: 99%